Case report: Retrograde endovascular recanalization of vertebral artery occlusion with non-tapered stump via the deep cervical collateral - Qiu, Han; Kang, Zhiming; Sun, Dong; Mei, Bin; Zhang, Junjian (Frontiers in Neurology, 2023)
Introduction: Vertebral artery (VA) occlusive disease is a major cause of posterior circulation ischemic stroke. Endovascular recanalization has been reported as a feasible treatment for patients with symptomatic VA occlusion refractory to optimal medical therapy. However, VA occlusion with non-tapered stump exhibits low technique success rate when treated by antegrade endovascular therapy because of increased difficulty in passing the guidewire into the occluded segment. Herein, we presented a novel endovascular approach to recanalize chronically occluded VA with non-tapered stump using a retrograde method via the deep cervical collateral, which has not been reported before. Case presentation: The present case was a patient with VA ostial occlusion with non-tapered stump and distal severe stenosis of the left VA who had recurrent posterior circulation transit ischemic attacks under optimal medical therapy. CT angiography demonstrated proximal non-tapered occlusion and distal severe stenosis of the left VA, and that the right VA did not converge with the left VA into basilar artery. Endovascular treatment was recommended and performed in this patient. However, antegrade endovascular recanalization of the left VA origin occlusion failed because the micro guidewire was unable to traverse the occluded segment. Fortunately, robust collateral from the deep cervical artery to the V3 segment of the left VA developed, in which we advanced the micro guidewire to the V3 segment of the left VA, and reversely passed the micro guidewire through the occluded segment. Then the occlusion and stenosis of the left VA was successfully resolved with angioplasty and stenting. After the procedure, the patient reported no neurological symptoms under medical therapy during 3-month follow-up. Conclusion: Antegrade endovascular recanalization of VA occlusion with a non -tapered stump is a challenge. Retrograde endovascular method via the cervical collateral may be an alternative for this type of VA occlusion, which requires further exploration.